PERANCANGAN SISTEM INFORMASI PENDATAAN CALON PENERIMA BEASISWA BAZNAS KABUPATEN ASAHAN - Suci Ramadhani; Isma Auli Mahrani; Ryandini Dwi Agusti; Riri Khairunnisa; Neni Mulyani (JURNAL TEKNISI, 2024)
Abstract: Poverty is a serious problem in developing countries, including Indonesia, which has an impact on limited access to education. To address this issue, BAZNAS (National Amil Zakat Agency) is present as a zakat management institution that aims to alleviate poverty through programs such as scholarships. However, in practice, there are obstacles in the effectiveness and efficiency of the process of data collection and input of scholarship recipients' files. This study aims to develop a design of an information system for data collection of scholarship recipients at BAZNAS Kabupaten Asahan to assist in the data collection and input process of scholarship recipients' files. This system uses MySQL database and PHP programming through visual studio code software, and functions as a recommendation tool in the data collection of scholarship recipients. With this information system, it is expected to help BAZNAS in improving the accuracy and efficiency of the data collection and input process of scholarship recipients' files, so that the scholarship program can be more targeted and have a greater impact in efforts to alleviate poverty through education. Keywords: baznas; scholarship; poverty Abstrak: Kemiskinan merupakan permasalahan serius di negara berkembang, termasuk Indonesia, yang berdampak pada keterbatasan akses pendidikan. Untuk mengatasi hal ini, lembaga BAZNAS (Badan Amil Zakat Nasional) hadir sebagai lembaga pengelola zakat yang bertujuan untuk mengentaskan kemiskinan melalui program-program seperti beasiswa. Namun, dalam praktiknya, terdapat kendala dalam efektivitas dan efisiensi dalam proses pendataan dan penginputan berkas calon penerima beasiswa. Penelitian ini bertujuan untuk membangun sebuah perancangan sistem informasi pendataan calon penerima beasiswa pada BAZNAS Kabupaten Asahan guna membantu proses pendataan dan penginputan berkas dari para calon penerima beasiswa. Sistem ini menggunakan database MySQL dan pemrograman php melalui software visual studio code, serta berfungsi sebagai alat rekomendasi dalam pendataan calon penerima beasiswa. Dengan adanya sistem informasi ini, diharapkan dapat membantu pihak BAZNAS dalam meningkatkan akurasi dan efisiensi dalam proses pendataan serta penginputan berkas calon penerima beasiswa, sehingga program beasiswa dapat lebih tepat sasaran dan memberikan dampak yang lebih besar dalam upaya mengentaskan kemiskinan melalui pendidikan.Kata Kunci: baznas; beasiswa; kemiskinan.